Overexpression of 14-3-3σ counteracts tumorigenicity by positively regulating p73 in vivo - GENG, CUIZHI (D.A. Spandidos, 2011)
14-3-3σ, one of the 14-3-3 family members, was initially identified as a human mammary epithelium-specific marker 1. The expression of 14-3-3σ is directly regulated by p53. It has been demonstrated that 14-3-3σ stabilizes p53 and enhances its transcriptional activity through the interaction with p53, suggesting that 14-3-3σ has a positive feedback effect on p53. Our previous study showed that 14-3-3σ is a direct transcriptional target of p73 and enhances the p73-mediated transcriptional as well as pro-apoptotic activity in vitro. In the present study, we explored the tumor-suppressive effect of 14-3-3σ by establishing a breast cancer xenograft nude mouse model with an inducible expression of 14-3-3σ or with an inducible expression of p53/p73 plus 14-3-3σ with ADR treatment. Tumor formation was then assayed. Moreover, 66 primary breast cancer specimens and paired tumor-free breast specimens obtained from the female patients were examined. Results showed that the expression of p73 and 14-3-3σ in breast cancer specimens was significantly lower than the tumor-free breast specimens and that 14-3-3σ expression was positively correlated with the expression of p73. Furthermore, overexpression of 14-3-3σ counteracts tumorigenicity by positively regulating p73 in p53-mutated or -deficient cancers in vivo. Therefore, our results may lead to the use of 14-3-3σ in the therapeutic application for the p53-mutated and p73-expressed breast cancer patients.